If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(w + -2) + -6w = -21 Reorder the terms: 3(-2 + w) + -6w = -21 (-2 * 3 + w * 3) + -6w = -21 (-6 + 3w) + -6w = -21 Combine like terms: 3w + -6w = -3w -6 + -3w = -21 Solving -6 + -3w = -21 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -3w = -21 + 6 Combine like terms: -6 + 6 = 0 0 + -3w = -21 + 6 -3w = -21 + 6 Combine like terms: -21 + 6 = -15 -3w = -15 Divide each side by '-3'. w = 5 Simplifying w = 5
| -2.06d+18=-10.48 | | 3a=144 | | 7m-9m=-12 | | x^2(x+9)+7(x+9)= | | -110=-4c-6c | | 3b+4=15 | | 5x+10=3x+24 | | 11x+(-6x)+11= | | 9r-8=6r+7 | | (x^4+y^2)(x^4-y^2)= | | 3(x+4)-(-4)=2x+8-4 | | 5x^6+5x^5-40x^4+35x^3= | | 2x-x=1.5 | | 4x-10=2x+12 | | x^2=(x-2)*(x+6) | | 3t+9t=60 | | m=n+8 | | 3x+5=5x-9 | | 7u+11.59=32.31 | | 3x+7=6x-11 | | 19x^7-8x^5+16x^4= | | 2x=(x-2)*(x+6) | | -3(1+2v)=90 | | (x-3)(x-1)(2x-5)=6 | | 3(2x-10)=-12 | | 2x*21=28(x+5) | | (x-3)(x-1)(2x-5)=12 | | -4a-6+5a=-3 | | 6x^6-7x^4+17x^3= | | 2x^3-x^2-16x+15=0 | | (5r-4)(6r-6)= | | 7h+13=230 |